2019
DOI: 10.2217/cer-2019-0074
|View full text |Cite
|
Sign up to set email alerts
|

Ferric carboxymaltose for patients with heart failure and iron deficiency in Italy: cost–effectiveness and budget impact

Abstract: Aim: To evaluate the cost–effectiveness of intravenous ferric carboxymaltose (FCM) versus placebo for the management of iron deficiency in patients with chronic heart failure in the Italian healthcare system and to estimate its impact on the national healthcare budget. Materials & methods: A Markov model was developed to project costs and health outcomes over 1 year, based on data from literature. Healthcare resources consumption was derived from an e-survey administered to clinicians. Costs were obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
11
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 31 publications
3
11
0
3
Order By: Relevance
“…Our study concluded that PBM was a cost-effective option and has cost-saving potential in hip and knee arthroplasties and CABG in Turkey. This finding is in line with examples from other health-care systems, 15 , 43 , 44 and is similar to results reported in earlier literature; it concludes that implementing just the first pillar of PBM can be a cost-effective option and may provide considerable cost-saving opportunities to the SSI. In the cost-effectiveness analysis, the incremental cost per avoided postoperative adverse event was used as the decision criterion.…”
Section: Discussionsupporting
confidence: 91%
“…Our study concluded that PBM was a cost-effective option and has cost-saving potential in hip and knee arthroplasties and CABG in Turkey. This finding is in line with examples from other health-care systems, 15 , 43 , 44 and is similar to results reported in earlier literature; it concludes that implementing just the first pillar of PBM can be a cost-effective option and may provide considerable cost-saving opportunities to the SSI. In the cost-effectiveness analysis, the incremental cost per avoided postoperative adverse event was used as the decision criterion.…”
Section: Discussionsupporting
confidence: 91%
“…This economic analysis was based on data for patients with a recent AHF episode, representing a very high‐risk subgroup of patients with HF; however, the findings are applicable to all patients with HF and align with those from prior economic analyses in patients with chronic HF and ID: in the FAIR‐HF trial, FCM was cost‐effective vs. placebo from UK, 27 Spanish 5 and Swedish 28 health service perspectives. Similarly, a pooled analysis of patient‐level data from FAIR‐HF, FER‐CARS‐01, CONFIRM‐HF and EFFICACY‐HF trials found that FCM was dominant vs. placebo in an Italian healthcare setting 19 and cost‐saving over 5 years in a French healthcare setting. 29 These data support our findings and suggest that FCM is cost‐effective in a broad spectrum of patients with HF and ID.…”
Section: Discussionmentioning
confidence: 97%
“…The difference in a small incremental cost for gain in QALYs, as for Italy, is in part due to the higher estimated background HF maintenance cost for Italy. The cost was derived from the work of Rognoni and Gerzeli 19 who, in performing an economic analysis of FCM in the Italian setting, reported costs for a model based on New York Heart Association (NYHA) classes. If these costs were lower, then, like the other countries, the intervention tends towards dominance.…”
Section: Discussionmentioning
confidence: 99%
“…The BI analyses of FCM in patients with CHF have also showed cost savings or a minimal BI in other European countries. A recent combined CEA and BI study within the Italian Healthcare System using the same model resulted in savings of e382 per patient per year 33 . In France, with a time horizon of 5 years, the savings were of e5 per patient (e2.5 in the first year) 34 , while in Romania, those were e9 per patient over 1 year 35 .…”
Section: Discussionmentioning
confidence: 99%